Immune Profiling and Quantitative Analysis Decipher the Clinical Role of Immune-Checkpoint Expression in the Tumor Immune Microenvironment of DLBCL - Xu-Monette, Ziju Y; Xiao, Min; Au, Qingyan; Padmanabhan, Raghav; Xu, Bing; Hoe, Nicholas; Rodríguez-Perales, Sandra; Torres-Ruiz, Raul; Manyam, Ganiraju C; Visco, Carlo; Miao, Yi; Tan, Xiaohong; et al. (Cancer immunology research, 2019)
PD-1/L1 and CTLA-4 blockade immunotherapies have been approved for 13 types of cancers and are being studied in diffuse large B-cell lymphoma (DLBCL), the most common aggressive B-cell lymphoma. However, whether both PD-1 and CTLA-4 checkpoints are active and clinically significant in DLBCL is unknown. Whether PD-1 ligands expressed by tumor cells or by the microenvironment of DLBCL are critical for the PD-1 immune checkpoint is unclear. We performed immunophenotypic profiling for 405 patients with DLBCL using a MultiOmyx immunofluorescence platform and simultaneously quantitated expression/coexpression of 13 immune markers to identify prognostic determinants. In both training and validation cohorts, results demonstrated a central role of the tumor immune microenvironment, and when its functionality was impaired by deficiency in tumor-infiltrating T cells and/or natural killer cells, high PD-1 expression (but not CTLA-4) on CD8 T cells, or PD-L1 expression on T cells and macrophages, patients had significantly poorer survival after rituximab-CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) immunochemotherapy. In contrast, tumor-cell PD-L2 expression was associated with superior survival, as well as PD-L1 CD20 cells proximal (indicates interaction) to PD-1 CD8 T cells in patients with low PD-1 percentage of CD8 T cells. Gene-expression profiling results suggested the reversibility of T-cell exhaustion in PD-1 /PD-L1 patients with unfavorable prognosis and implication of / , and upregulation in the microenvironment dysfunction with PD-L1 expression. This study comprehensively characterized the DLBCL immune landscape, deciphered the differential roles of various checkpoint components in rituximab-CHOP resistance in DLBCL patients, and suggests targets for PD-1/PD-L1 blockade and combination immunotherapies.